1996
DOI: 10.1136/gut.39.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Variability of gastrointestinal transit in healthy women and men.

Abstract: Background and Aims-Measurements of gastrointestinal transit are made in clinical and research gastroenterology, yet their intrinsic variability is not well characterised. In particular, an influence of hormones on transit has been proposed as the basis for gastrointestinal symptoms that vary with the menstrual cycle. Our aims were to quantify individual differences in transit during the menstrual cycle in healthy women and to compare these with the intrinsic variability in healthy men. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
212
5
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(235 citation statements)
references
References 49 publications
16
212
5
2
Order By: Relevance
“…Only women were recruited for the present study, because it has been suggested that bowel function differs between the sexes. In several studies, women have had harder stools than men (Degen and Phillips, 1996a), and colonic transit has been faster in men than in women (Hinds et al, 1989;Degen and Phillips, 1996b;Chan et al, 2004). The menstrual cycle was not taken into account, because several studies have confirmed that sex hormones do not have any major effect on bowel frequency, stool weight (Kamm et al, 1989) or transit time (Hinds et al, 1989;Turnbull et al, 1989;Degen and Phillips, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…Only women were recruited for the present study, because it has been suggested that bowel function differs between the sexes. In several studies, women have had harder stools than men (Degen and Phillips, 1996a), and colonic transit has been faster in men than in women (Hinds et al, 1989;Degen and Phillips, 1996b;Chan et al, 2004). The menstrual cycle was not taken into account, because several studies have confirmed that sex hormones do not have any major effect on bowel frequency, stool weight (Kamm et al, 1989) or transit time (Hinds et al, 1989;Turnbull et al, 1989;Degen and Phillips, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…2). The intragastric pH in healthy individuals is in the pH 1.3-2.5 range and the 50 % emptying of stomach contents requires about 2.5-3 h (Degen & Phillips, 1996;Kong & Singh, 2008). Taken together, the infectivity of ReCVs and perhaps human NoVs would be significantly jeopardized in the stomach without some protective mechanism.…”
Section: Recv-hbga Interactionsmentioning
confidence: 96%
“…There is significant intraindividual variation in gastric emptying rates of 12-15%, even in healthy individuals (25,34). The relationship of gastric emptying rates of the 200-kcal meal to symptoms remains controversial (122).…”
Section: Gastric Emptying Scintigraphymentioning
confidence: 99%